Awareness, perception, attitude, and knowledge regarding complementary and alternative medicines (cams) among the pharmacy and medical students of a public university in Saudi Arabia - Rizwan Ahmad; Atta A Naqvi; Niyaz Ahmad; Mohamed Baraka; Mohammad Mastour; Saleh Al Sharedah; Shatha Al Ghamdi; Ghada Al Rabae; Mastour S Al Ghamdi (Archives of Global Professionals, 2017)
Introduction: The use of natural products, that is, herbs for clinical and domestic purposes, is quite common in Saudi Arabia. Studies have reported an increasing use of complementary and alternative medicines (CAMs). This study aims to investigate the perception, attitude, and knowledge of the students regarding CAMs and their use. Materials and Methods: A quantitative, cross-sectional study targeting the students of the pharmacy and medical colleges at the University of Dammam, Saudi Arabia was conducted for a 6-month duration. It employed a survey questionnaire termed as CAMs inventory. Results: The majority of the respondents were females (N = 180, 60.8%), and a major segment (N = 170, 57.4%) belonged to the age group between 21 and 23 years. Nearly half of the students (N = 121, 40.9%) strongly agreed on the need for integration of CAMs-related courses in medical and allied health education, and a similar proportion (N = 129, 43.6%) of the target population acknowledged using CAMs, based on family recommendations (N = 134, 45.3%). Half of the students (N = 142, 48%) had no knowledge about CAMs. Some of the CAMs were more prevalent in males and vice versa (P value <0.05). Conclusion: A positive perception and attitude toward CAMs was observed. It is influenced by their traditional use and partly by the recent induction of CAMs-related education in pharmacy. The majority of the students agreed on integrating CAMs-related courses in their curriculum. It was also observed that the knowledge regarding the subject was inadequate. Lastly, gender has the potential to influence the use of particular CAMs.